ESTETIKA, ETIKA, DAN IDENTITAS DALAM PEMBELAJARAN MUSIK TRADISIONAL UNTUK ANAK USIA DINI - Christina, Dina; Yetti, Eliendra; Herdiati, Dian (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
Traditional music learning in early childhood plays an important role not only in the development of musical abilities, but also in the formation of character, emotional sensitivity, and the strengthening of cultural identity. This article aims to examine traditional music education from a philosophy of education perspective by positioning aesthetics, ethics, and identity as the three main pillars of arts education. The study employs a normative qualitative approach through a literature review and conceptual reflection on traditional music learning practices in early childhood education institutions in Indonesia. The findings indicate that traditional music functions as a holistic educational medium that integrates aesthetic experiences, the cultivation of moral virtues, and the reinforcement of children’s cultural identity. Aesthetic values are reflected in the process of appreciating harmony, rhythm, and musical expression, which foster children’s sensitivity and creativity. Ethical dimensions develop through collective musical practices that instill discipline, responsibility, cooperation, and empathy. Meanwhile, identity values play a role in strengthening a sense of nationalism and appreciation for local cultural heritage amid globalization. These findings affirm that traditional music learning is a sustainable educational strategy that supports the formation of well-rounded individuals. ABSTRAK Pembelajaran musik tradisional pada anak usia dini memiliki peran penting tidak hanya dalam pengembangan kemampuan musikal, tetapi juga dalam pembentukan karakter, kepekaan rasa, dan penguatan identitas budaya. Artikel ini bertujuan untuk mengkaji pembelajaran musik tradisional dari perspektif filsafat pendidikan dengan menempatkan estetika, etika, dan identitas sebagai tiga pilar utama pendidikan seni. Penelitian menggunakan pendekatan kualitatif normatif melalui studi literatur dan refleksi konseptual terhadap praktik pembelajaran musik tradisional di lembaga pendidikan anak usia dini di Indonesia. Hasil kajian menunjukkan bahwa musik tradisional berfungsi sebagai media pendidikan holistik yang mengintegrasikan pengalaman estetis, pembentukan kebajikan moral, serta penguatan jati diri budaya anak. Nilai estetika tercermin dalam proses apresiasi harmoni, ritme, dan ekspresi musikal yang menumbuhkan kepekaan dan kreativitas anak. Dimensi etika berkembang melalui praktik musikal kolektif yang menanamkan nilai disiplin, tanggung jawab, kerja sama, dan empati. Sementara itu, nilai identitas berperan dalam memperkuat rasa kebangsaan dan kecintaan terhadap warisan budaya lokal di tengah arus globalisasi. Temuan ini menegaskan bahwa pembelajaran musik tradisional merupakan strategi pendidikan berkelanjutan yang mendukung pembentukan manusia seutuhnya.